Konseling spiritual untuk mengatasi siswa bermasalah di Madrasah Aliyah Negeri 3 Sleman - Imelda Puspita Putri; Syamsudin (At Turots: Jurnal Pendidikan Islam, 2023)
Guidance and counseling play a crucial role in shaping the behavior of students in madrasahs or schools. One counseling approach is the spiritual approach, which aims to help adolescents overcome negative behaviors, develop a sense of responsibility, and grow in truth. This study aims to: (1) analyze the forms of spiritual counseling at Madrasah Aliyah Negeri (MAN) 3 Sleman, and (2) analyze how the implementation of spiritual counseling at Madrasah Aliyah Negeri (MAN) 3 Sleman addresses student issues. This research employs a case study approach. Data collection is conducted through observation and interviews. The research subjects consist of Guidance and Counseling (BK) teachers as well as Islamic Education (PAI) teachers. Based on the research findings, it is revealed that spiritual counseling at MAN 3 Sleman involves several aspects, such as guiding students to perform congregational prayers, improving worship practices, and enhancing relationships with parents and friends. This spiritual counseling is not only provided to students facing issues but is available to all students. When addressing student problems, BK teachers do not employ punitive methods, but rather use a discussion-based approach. BK teachers first understand the students' issues, then guide them to improve their worship practices and social relationships with parents and peers. Subsequently, BK teachers and students engage in discussions to collectively resolve the students' issues.